Variation of Fingerprint Patterns Among Students at OSO University Based on Ethnicity and Gender - Wahyuni, Muftiah Yasi Dwi; Raynaldo, Adityo; Marista, Etha; Bibas, Elpe; Kurnia, Fitriyan; Linda, Riza (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Fingerprints are utilized for personal identification, as well as to identify ethnicity, blood type and gender. They are permanent and remain unchanged throughout lifetime, unless an injury causes skin damage. This study aims to examine the variation in fingerprint patterns among students at OSO University, considering ethnic and gender differences. This study used a purposive sampling method and at least 50 fingerprint samples from students at the Faculty of Natural Sciences and Marine Science, OSO University. Generally, the loop fingerprint pattern is found in approximately 54.67% of the total sample of students. The loop fingerprint pattern is most commonly found in the Bugis, Malay and Javanese ethnic, while the Dayak ethnic predominantly has the whorl pattern. The arch fingerprint pattern is only found in the Dayak ethnic group. It can be assumed that the arch pattern may act as a distinguishing characteristic among ethnic groups in West Kalimantan. This study can contribute to forensic science, especially in identifying individuals based on fingerprint patterns associated with ethnicity and gender. This research can provide as a foundation for further studies that explore the relationship between fingerprint patterns and other demographic factors, such as age or geographic location.